Testicular and epididymal dysfunctions: searching a new index for the differential diagnosis - Fernando T. Andrade-Rocha; Walter D. Cardona-Maya (Urología Colombiana)
Objective: This proof-of-principle aims to develop an index to aid the differential diagnosis of disorders affecting testicular and/or epididymis. A total of 202 subject data were evaluated in two groups: fertile men with children naturally conceived within 1 year of unprotected intercourse (n = 36) and infertile men (n = 166) who had attempted a pregnancy more than 1 year with unprotected intercourse. Materials and methods: Semen parameters (sperm count, vitality, motility, morphology, and hypoosmotic swelling test [HOST]) were evaluated. The index was calculated by dividing the percentage HOST by the percentage of sperm progressive motility in the fertile group (n = 36). Results: A normal range from 1.23 to 1.53 was determined. Using this index, the outcomes of semen analysis from infertile men were grouped in three study groups: below 1.23 (n = 24), normal (n = 44), and higher than 1.53 (n = 98). These parameters were significantly decreased in semen with normal range (p < 0.01) and in indexes higher than 1.53 (p < 0.0001). Receiver operating characteristic curves compared progressive motility and morphology in infertile men with indexes higher than 1.53 shows that semen samples with normal sperm progressive motility and morphology did not suggest dysfunctions in testis and epididymis. Semen samples with asthenozoospermia suggested epididymal dysfunction (area under the curve [AUC] 0.889, confidence interval [CI] 0.783-1), whereas semen samples with teratoasthenozoospermia suggested dysfunction in both testicles and epididymis (AUC 0.891, CI 0.77-1). Conclusions: The current index proof-of-principle of the success of such a strategy provides valuable information about whether a disorder individually affects testicular and/or epididymal function.